Anti-Idiotypic Antibodies Specific to prM Monoantibody Prevent Antibody Dependent Enhancement of Dengue Virus Infection - Wang, Miao; Yang, Fan; Huang, Dana; Huang, Yalan; Zhang, Xiaomin; Wang, Chao; Zhang, Shaohua; Zhang, Renli (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue virus (DENV) co-circulates as four serotypes (DENV1-4). Primary infection only leads to self-limited dengue fever. But secondary infection with another serotype carries a higher risk of increased disease severity, causing life-threatening dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Serotype cross-reactive antibodies facilitate DENV infection in Fc-receptor-bearing cells by promoting virus entry via Fcγ receptors (FcγR), a process known as antibody dependent enhancement (ADE). Most studies suggested that enhancing antibodies were mainly specific to the structural premembrane protein (prM) of DENV. However, there is still no effective drugs or vaccines to prevent ADE. In this study, we firstly confirmed that both DENV-2 infected human sera (anti-DENV-2) and DENV-2 prM monoclonal antibody (prM mAb) could significantly enhance DENV-1 infection in K562 cells. Then we developed anti-idiotypic antibodies (prM-AIDs) specific to prM mAb by immunizing of Balb/c mice. Results showed that these polyclonal antibodies can dramatically reduce ADE phenomenon of DENV-1 infection in K562 cells. To further confirm the anti-ADE effect of prM-AIDs in vivo, interferon-α and γ receptor-deficient mice (AG6) were used as the mouse model for DENV infection. We found that administration of DENV-2 prM mAb indeed caused a higher DENV-1 titer as well as interleukin-10 (IL-10) and alaninea minotransferase (ALT) in mice infected with DENV-1, similar to clinical ADE symptoms. But when we supplemented prM-AIDs to DENV-1 challenged AG6 mice, the viral titer, IL-10 and ALT were obviously decreased to the negative control level. Of note, the number of platelets in peripheral blood of prM-AIDs group were significantly increased at day 3 post infection with DENV-1 compared that of prM-mAb group. These results confirmed that our prM-AIDs could prevent ADE not only in vitro but also in vivo, suggested that anti-idiotypic antibodies might be a new choice to be considered to treat DENV infection.